2020
DOI: 10.1002/slct.202000463
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Application of Polyacrylamide‐Polystyrene/Bentonite Nanocomposite as an Effective Immobilizing Adsorbent for Remediation of Soil

Abstract: Heavy metals are among the most important environmental pollutants. However, little attention has been devoted to immobilizing or fixing metal ions in soil for remediation of soil. Here, a novel and inexpensive, polymer nanocomposite (polyacrylamide-polystyrene/bentonite) is introduced for successful immobilization of cadmium (Cd) and lead (Pb) cations in the soil. The synthesized nanocomposite structure was characterized by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy/Energy-Dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Generally, it is expected that competition between H 2 O 3 M 2+ ions reduce adsorption capacity at a low pH, [ 37 ], therefore in the higher acidic regions, preferably at pH values ranging from 4-7 most adsorbents perform better in comparison to their performances in lower acidic regions. As the adsorption extent is withered in lower acidic regions, increasing pH thereby increases adsorption, and this is one of the dependent variables in adsorption affecting the efficiency of many adsorbents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it is expected that competition between H 2 O 3 M 2+ ions reduce adsorption capacity at a low pH, [ 37 ], therefore in the higher acidic regions, preferably at pH values ranging from 4-7 most adsorbents perform better in comparison to their performances in lower acidic regions. As the adsorption extent is withered in lower acidic regions, increasing pH thereby increases adsorption, and this is one of the dependent variables in adsorption affecting the efficiency of many adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ], prepared a Polyacrylamide-polystyrene/Bentonite nanocomposite for immobilizing Cd 2+ and Pb 2+ ions in the soil, and in this study, he discusses the adsorption efficiency of the nanocomposite in comparison to polyacrylamide or bentonite alone, which was found to be quite better, hereby signifying the presence of multiple material properties in a single adsorbent resulting in enhanced adsorption capacity [ 37 ]. Their results showed that the adsorption of Cd 2+ and Pb 2+ ions by bentonite occurs happens via cation exchange, and even though the base exchange ability of bentonite is limited, there is again adsorption of these metal ions by the polymer which takes place via the interactions existing between the Oxygen and Nitrogen functional groups of the polymer and adsorbate ion [ 37 ]. Again, these however, these relations plus those of bentonite maybe and or are limited, and could not possibly aid a successful removal of Cd 2+ and Pb 2+ ions from the sorbate, hence the room for innovation of such composites to improve their selectivity and adsorption properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The addition of Acrylamide (AM) significantly improves the water absorption of the product, its own thermal stability and salt resistance is also improved. [39][40][41][42] Bentonite is used in the following fields: (1) Bentonite mud can be used as drilling fluid. The addition of bentonite to concrete can significantly improve the durability, compressive strength, and corrosion resistance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…St is easy to prepare, low cost, hard and brittle, and through grafting, toughens NR while improving its own brittleness 38 . The addition of Acrylamide (AM) significantly improves the water absorption of the product, its own thermal stability and salt resistance is also improved 39–42 . Bentonite is used in the following fields: (1) Bentonite mud can be used as drilling fluid.…”
Section: Introductionmentioning
confidence: 99%